Hubert De Vries - Lampo, Hubert; Kinsbergen, Andries (Antwerpen : Artiestenfonds, 1967)
Bibliotheek Camille Huysmans
Dedicator: De Vries, Hubert, dedicatee: Huysmans, Camille
Nederlands
Monografie
Keywords: schilderkunst